Islam and international relations exploring community and the limits of universalism - Sheikh, Faiz (Rowman & Littlefield, 2016)
This book explores an Islamic approach to the international, showing that Islam can contribute keen insights into how we do IR, and how we might change that practice to be more inclusive, while also highlighting the limits of an Islamic International Relations.